Accelerating Poverty Reduction in Africa - Beegle, Kathleen; Christiaensen, Luc (Washington, DC: World Bank, 2019)
Sub-Saharan Africa's turnaround over the past couple of decades has been dramatic. After many years in decline, the continent's economy picked up in the mid-1990s. Along with this macroeconomic growth, people became healthier, many more youngsters attended schools, and the rate of extreme poverty declined from 54 percent in 1990 to 41 percent in 2015. Political and social freedoms expanded, and gender equality advanced. Conflict in the region also subsided, although it still claims thousands of civilian lives in some countries and still drives pressing numbers of displaced persons.